2005
DOI: 10.4049/jimmunol.175.6.3955
|View full text |Cite
|
Sign up to set email alerts
|

Gender Bias in Theiler’s Virus-Induced Demyelinating Disease Correlates with the Level of Antiviral Immune Responses

Abstract: Multiple sclerosis is an immune-mediated disease of the CNS and shows a sex-biased distribution in which 60–75% of all cases are female. A mouse model of multiple sclerosis, Theiler’s murine encephalomyelitis virus (TMEV)-induced demyelinating disease, also displays a gender bias. However, in the C57L/J strain of mice, males are susceptible to disease whereas females are completely resistant. In this study we determined the gender differences in the TMEV-specific immune response, which may be responsible for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 57 publications
(42 reference statements)
3
28
0
Order By: Relevance
“…Estrogen is known to regulate the differentiation, survival, and function of diverse immune cells (30,37,50). In addition, female mice produce significantly more specific antibody in response to various infections (27). The difference in gender may also be explained by the immunoregulatory effect of testosterone, which is know to act directly on CD4…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen is known to regulate the differentiation, survival, and function of diverse immune cells (30,37,50). In addition, female mice produce significantly more specific antibody in response to various infections (27). The difference in gender may also be explained by the immunoregulatory effect of testosterone, which is know to act directly on CD4…”
Section: Discussionmentioning
confidence: 99%
“…Mice were perfused with sterile Hanks' balanced salt solution (HBSS), and excised brains and spinal cords were homogenized. CNS-infiltrating mononuclear cells (MNCs) were then enriched in the bottom one-third fraction of a continuous 100% Percoll gradient (Pharmacia, Piscataway, NJ) after centrifugation at 27,000 ϫ g for 30 min as previously described (14).…”
Section: Methodsmentioning
confidence: 99%
“…In general, highaffinity CD8 ϩ T cells are preferentially tolerized by deletion or anergy in vivo. In fact, the relative levels of IFN-␥-producing cells upon stimulation with serial 10-fold-decreased epitope peptide concentrations indicated that functional avidity to the dominant epitope (VP3 159-166 ) is 50-and 100-fold higher than those to the subdominant epitopes (VP3 173-181 and VP1 [11][12][13][14][15][16][17][18][19][20] , respectively) (data not shown). These results are consistent with the preferential reduction of high-affinity VP3 159-166 -specific CD8 ϩ T cells over low-affinity subdominant epitope-reactive CD8 ϩ T cells.…”
Section: Sjl P1-tg Mice Immunized With Uv-tmev Exhibit Lower Levels Omentioning
confidence: 99%
See 1 more Smart Citation
“…Brains and spinal cords were removed, minced with steel mesh, and treated with collagenase IV and DNase I (Sigma) for 45 min at 37°C. Mononuclear cells were isolated after 100% Percoll continuous gradient centrifugation at 27,000 ϫ g for 30 min as previously described (16).…”
Section: Methodsmentioning
confidence: 99%